Titin Mutation Is Associated With Tumor Mutation Burden and Promotes Antitumor Immunity in Lung Squamous Cell Carcinoma - Xie, Xiaona; Tang, Yemeng; Sheng, Jueqi; Shu, Pingping; Zhu, Xiayan; Cai, Xueding; Zhao, Chengguang; Wang, Liangxing; Huang, Xiaoying (Frontiers in Cell and Developmental Biology, 2021)
Lung squamous cell carcinoma (LUSC) is a leading cause of incidence and mortality worldwide. Recently, immune therapy has a shift the paradigm in LUSC patients, merely a little number of patients with non-small cell lung cancer (NSCLC) at advanced stages respond well to immune checkpoint blockade (ICB) therapy, and tumor mutation burden (TMB) is a valuable independent indicator of response to immune therapy. However, specific gene mutations and their relationship with TMB and tumor-infiltrating immunocytes in LUSC are still unclear. In the present paper, our team analyzed the somatically mutated genes from the ICGC (International Cancer Genome Consortium) and TCGA (The Cancer Genome Atlas) datasets, and discovered that 16 frequent gene mutations were occurred in both cohorts, including ZFHX4, MUC16, FLG, TP53, LRP1B, TTN, SYNE1, RYR2, CSMD3, USH2A, MUC17, DNAH5, FAM135B, COL11A1 and RYR3. Interestingly, only mutated TTN was related to higher TMB and prognostic outcomes among the 15 mutated genes. Moreover, according to the CIBERSORT algorithm, we revealed that TTN mutation enhanced the antitumor immune response. In conclusion, TTN may have important clinical implications for relevant immune therapy of Lung squamous carcinoma.